Effects of GA3 on vegetative growth in strawberry - Fagherazzi A.F.* (2017)
The use of growth regulators is already a common practice in modern horticulture. They provide several benefits simplifying and enhancing fruit production. In commercial strawberry production, the main growth regulator used and researched is gibberellic acid (GA3), mostly modifying the productive characteristics of plants, such as early flowering and increasing fresh fruit weight. However, the effects of the application of GA3 in nursery conditions are still quite unknown. The objective of this study is to evaluate the effect of spraying different doses of GA3 to vegetative characteristics in nursery plants of the strawberry cultivar 'Pircinque'. Treatments consisted in four different doses, 0 (control), 40, 80 and 160 mg L-1 of exogenous GA3. The experimental design was completely randomized with five replications. The analyzed variables were: total number of rhizomes, total length of the stolons, height and total number of runners emitted by plant, fresh and dry weight of the stolons. For the number of rhizomes and the length of stolons there were no significant differences. Control had indeed the highest fresh and dry weight of the stolons. An increase in the plant height and in the total number of runners emitted by the plant due to the increase in GA3 was observed. It is concluded that the foliar spraying with high concentrations of gibberellic acid promotes changes in vegetative characteristics and contributes to the development of runners.